Bridging the Gaps: A Bibliometric Key Theme Analysis in Multicultural Education Research (2019-2024) - Jobeda khanom; Tarequl Islam; Mahmudulhassan Mahmudulhassan (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
The goal of this study is to perform a thorough bibliometric analysis of multicultural education research. This study examines the field's publication trends, important themes, influential authors, and intellectual structure using a quantitative methodology. The Scopus database was used to gather a dataset of 744 papers published between 2019 and 2024. Throughout the study period, the number of publications about multicultural education steadily increased, according to the analysis. Diversity, cultural competency, teacher preparation, and curriculum creation are among the major topics that have been recognized. In terms of research production, the United States surpassed the Netherlands and the United Kingdom as the top three nations.